Doped Ceria Nanoparticles with Reduced Solubility and Improved Peroxide Decomposition Activity for PEM Fuel Cells. Issue 2 (5th February 2021) - Baker, Andrew M.; Stewart, S. Michael; Ramaiyan, Kannan P.; Banham, Dustin; Ye, Siyu; Garzon, Fernando; Mukundan, Rangachary; Borup, Rod L.
Abstract : Ceria nanoparticles (NPs) have unique catalytic properties which make them suited to scavenge degrading radical species and their precursor peroxides during PEM fuel cell operation. However, in the acidic environment of the fuel cell, ceria dissolves and the resulting cations migrate within the MEA, causing performance and durability losses. In this work, ex situ testing was used to evaluate the peroxide decomposition, selectivity towards radical generation, and solubility of Gd, Pr, and Zr-doped ceria NPs over a range of crystallite sizes and dopant levels. These doped materials exhibit better peroxide scavenging activity and dissolution resistance than undoped ceria. In these materials, activity is largely governed by increased surface area due to high internal porosity at smaller crystallite sizes compared to undoped ceria. Of the compounds tested, ceria NPs doped with 15 at% Zr (10 nm) and 5 at% Pr (17 nm) exhibited greater dissolution resistance than undoped ceria. Stabilization of the former doped NPs is attributed to crystallite agglomeration, while the increased stability of the latter is proposed to be due to its internally-porous, mesoscale structure suggested by its sorption isotherm. Both materials are more dissolution-resistant and active peroxide decomposers compared to undoped ceria but exhibit increased byproduct radical generation.